METODE DAN SUMBER ILMU PENGETAHUAN DALAM ISLAM - Ariny Tamamul Minnah; Sudirman (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2024)
Science in Islam is in-depth knowledge that comes from Allah's revelation. This research aims to examine science from an Islamic perspective through three main aspects: the definition of science, the methods applied, and the main sources underlying it. This research uses a literature study method, by examining relevant primary and secondary data sources. Analysis is carried out through content analysis to obtain objective insights from the text. The data collected is then processed using descriptive methods, so that this research can provide accurate information about the development of science in Islamic education. Science is listed in the Koran and is systematic. Research methods are divided into deductive, which starts from general assumptions to specific conclusions, and inductive, which observes specific phenomena to draw general conclusions. Sources of knowledge include the Koran, hadith, reason, heart and senses. The combination of revelation, reason and sensory experience, together with deductive and inductive methods, forms a holistic understanding of science in the context of education and knowledge development. Science, which is reflected in various terms in the Al-Qu'an, has deep and varied meanings, including knowledge, intelligence, and confidence. In Islamic epistemology, the source of knowledge consists of Allah's revelation through the Koran and hadith as the main foundation, and reason, heart and senses as complements.